THE USE OF ANTIBIOTICS IN FOOD ANIMALS - A THREAT TO HUMAN HEALTH - Rozalina Yordanova; Magdalena Platikanova; Petya Hristova (Peytchinski Publishing, 2024)
Background: Antibiotics are widely used in food animals to prevent disease, promote growth and maintain productivity. Modern animal production practices involve regular use of antimicrobials, but abusive use can lead to harmful consequences. The aim of this review was to provide comprehensive information regarding the risk of regular application of antibiotics in food animals, the potential consequences and impact on human health, and options for the prevention of antibiotic resistance in the food chain. Review Results: Although organizations such as WHO, UN, and EU have taken steps to reduce and limit the use of antibiotics in animals, these are proving insufficient in developing countries. In many countries, the antibiotics used in animals appear to exceed that in humans. The abuse in food animals promotes the development of antibiotic-resistant bacteria and resistance genes that can be transmitted to humans through food consumption and direct contact with animal food or environment mechanisms. This can lead to human infections with antibiotic-resistant bacteria, causing treatment failure and, therefore, more severe and longer-lasting illnesses, increased hospitalization rates, more deaths and higher costs to society. Furthermore, as food animals and animal-derived foods are traded globally, they contribute to antibiotic resistance in countries far from where the problem originates. Conclusion: Overcoming the problem of antibiotic resistance requires a multidisciplinary approach with effective action coordination and information exchange between the agricultural, food, veterinary and health sectors. Through international cooperation, efforts should focus on reducing unnecessary antibiotics use and reducing the spread of antibiotic-resistant bacteria, but national-level action on antibiotic resistance and food safety is also essential.